Is there a Strategy in China’s Health Official Development Assistance to African Countries ? - (:unkn) unknown (My University, 2019)
China now ranks among the top ten bilateral donors for health official development assistance (ODA) in Africa. Our objective is to study the factors associated with Chinese health ODA to Africa in the 2006-2013 period. Chinese health ODA is measured using the AidData’s Global Chinese Official Finance Dataset, 2000-2014, Version 1.0. In total, 345 health aid projects were financed by China in Africa between 2006 and 2013, accounting for a total amount of 2014 US$764 million. Over the 2006-2013 period, Chinese health aid appears responsive to the economic needs of African countries and unrelated to the quality of their governance. While we find that China favors countries with limited ability to finance health projects, Chinese health aid allocation is poorly related to direct health needs of African countries. We find no evidence that Chinese health aid is directed to natural resources-rich countries while our results indicate the existence of an association between economic ties with China and the volume of Chinese health ODA received. Finally, our results confirm the idea that health aid might be used by China as part of its foreign policy since non-adherence to the one-China policy makes the receipt of Chinese health aid very unlikely.
Keywords: African Research